2014
DOI: 10.1063/1.4863683
|View full text |Cite
|
Sign up to set email alerts
|

Schottky junction solar cells based on graphene with different numbers of layers

Abstract: We have investigated the performance of Schottky junction solar cells based on silicon and graphene with 1–6 layers. The open-circuit voltage of solar cells shows an increase when increasing the number of graphene layers. However, the power conversion efficiency and short-circuit current density increase monotonically when the number of graphene layers is less than 4 and reduces as the number of graphene layers further increases. Our results demonstrate that the number of layers related to the work function an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…The V OC of the Au NPs/FLG/Si solar cells (0.40-0.45 V) is much higher than those of the Au NPs/ MLG/Si devices (0.26-0.42 V), which is in good agreement with the previous works and can be attributed to the increased work function of graphene with more layers. 5,18 Unlike V OC , the value of J SC is found to exhibit an initial rise when the Au thickness is less than 9 nm, giving rise to a maximum value of 30.5 mA/cm 2 for the Au NPs/MLG/Si cell and 31.8 mA/cm 2 for the Au NPs/FLG/Si device, and then display a slight decrease as the Au initial thickness over 9 nm. The FF shows a similar dependence on the Au thickness as J SC , which increases from 25% for the reference FLG/Si cell to 49% for the Au NPs/FLG/Si cell with an initial Au thickness of 9 nm, as shown in Fig.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The V OC of the Au NPs/FLG/Si solar cells (0.40-0.45 V) is much higher than those of the Au NPs/ MLG/Si devices (0.26-0.42 V), which is in good agreement with the previous works and can be attributed to the increased work function of graphene with more layers. 5,18 Unlike V OC , the value of J SC is found to exhibit an initial rise when the Au thickness is less than 9 nm, giving rise to a maximum value of 30.5 mA/cm 2 for the Au NPs/MLG/Si cell and 31.8 mA/cm 2 for the Au NPs/FLG/Si device, and then display a slight decrease as the Au initial thickness over 9 nm. The FF shows a similar dependence on the Au thickness as J SC , which increases from 25% for the reference FLG/Si cell to 49% for the Au NPs/FLG/Si cell with an initial Au thickness of 9 nm, as shown in Fig.…”
mentioning
confidence: 91%
“…Furthermore, it has been reported that the numbers of layers of graphene had significant effects on the performance of Gr/Si Schottky junction solar cells. 5,18 Thus, in the present work, both MLG and FLG were utilized to fabricate the Au NPs/Gr/Si solar cells, and the corresponding J-V characteristics under illumination are shown in Figs. 2(b) and 2(c), respectively.…”
mentioning
confidence: 99%
“…But, the reflectivity of graphene increases with increasing graphene layers [42]. As the performance of Schottky junction solar cells dependence on the different numbers of layers of graphene has been reported by Li et al [13], we only consider the effect of tuning monolayer graphene work function on the performance of G/n-Si_SBSC. As shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, graphene/silicon (G/Si) structure has been studied and shows diode characteristics as a Schottky junction [12]. In particular, Schottky barrier solar cells (SBSC) obtained by deposition of graphene sheets on n-Si wafer has been reported [3,13]. The major process for the fabrication of G/Si solar cells can be accomplished via a solution transfer process at room temperature in air.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have been reported in term of graphene for optoelectronic applications, include solar cell [1][2][3][4]. Most of them still reach relatively low power conversion efficiency (<5% PEC) as a consequence many efforts continuouslly carried out in order to get a better achievement either experimentally or simulation studies.…”
Section: Introductionmentioning
confidence: 99%